2013
DOI: 10.1007/s10439-013-0931-2
|View full text |Cite
|
Sign up to set email alerts
|

A Validation of Two-Dimensional In Vivo Regional Strain Computed from Displacement Encoding with Stimulated Echoes (DENSE), in Reference to Tagged Magnetic Resonance Imaging and Studies in Repeatability

Abstract: Fast cine displacement encoding with stimulated echoes (DENSE) has comparative advantages over tagged MRI (TMRI) including higher spatial resolution and faster post-processing. This study computed regional radial and circumferential myocardial strains with DENSE displacements and validated it in reference to TMRI, according to American Heart Association (AHA) guidelines for standardized segmentation of regions in the left ventricle (LV). This study was therefore novel in examining agreement between the modalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 45 publications
(129 reference statements)
6
76
0
Order By: Relevance
“…On the other hand, other authors, including Augustine et al,18 using feature‐tracking, Neizel et al19 using SENC, and Kuznetsova et al20 using echocardiography found that women had similar circumferential and longitudinal strain to men. DENSE,1 tagging,8 phase contrast MR,10 and feature tracking21 use different techniques to analyze strain, which could account for some of the differences in strain values observed using these different methods 22…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other authors, including Augustine et al,18 using feature‐tracking, Neizel et al19 using SENC, and Kuznetsova et al20 using echocardiography found that women had similar circumferential and longitudinal strain to men. DENSE,1 tagging,8 phase contrast MR,10 and feature tracking21 use different techniques to analyze strain, which could account for some of the differences in strain values observed using these different methods 22…”
Section: Discussionmentioning
confidence: 99%
“…In that work, a coarse-to-fine B-spline scheme allows for the effective and robust computation of the displacement, and also a pyramidal refinement scheme helps to deal with large motions. From the myocardial motion field, various further studies have been realized in order to extract motion-related information, such as myocardium segmentation (Dietenbeck et al, 2014), local deformation (Kar et al, 2014;Oubel et al, 2012), and local region tracking (Arif et al, 2014;Luo et al, 2014;Sun et al, 2011). For these information extraction methods, the key point is to estimate an accurate myocardium motion field.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were significant differences between the scar and control groups, the AUC was small, preventing the use of radial strain for diagnostics. The high variability of radial strain in healthy individuals has also been demonstrated in other studies [148].…”
Section: Papermentioning
confidence: 50%